O americanismo em Domingo Faustino Sarmiento: paradoxo e desilusão - Porto, Diego Gobo (2010)
This study analyses Sarmiento’s ideas for the construction of Argentina. He believed that Argentina, for being under the dominion of barbarism, needed to undertake a series of reforms in order to achieve moral and material progress. The major means of this national (re)construction plan were the foundation of a system of public schools, intended to embrace the whole society, as well as the fostering of immigration. The north-American experience was his major frame of reference. Under this light, he can be regarded alongside the americanists (intellectuals who proposed the north-American way to accomplish the task of modernization). The reforms he addressed, however, were to be taken on by the State itself. In this specific aspect he diverged from other americanists. Actually, the defense of the central role of the State as a condition for the realization of such reforms constituted a paradox. Even under this direction the reforms did not manage to realize all the goals Sarmiento had set to be fulfilled. In spite of providing a certain economic progress, they did not produce the long-wished civilizational progress. Facing this reality, Sarmiento became frustrated about the possibility of founding a virtuous republic, what can be asserted as one of the main tones of his last writings. This work analyses, precisely, both the paradox and the disenchantment that marked Sarmiento’s thought in the last period of his life.